Kolaborasi Ekoteologi: Mewujudkan Desa Bersih Dan Harmonis di Lau Gumba - Tri Inda Fadhila Rahma; Muhammad Ilham; Nadia Gunawan; Vressillia Witama; M. Rangga Syahputra Saragih; Suci Ramadayani (Jurnal Pengabdian Masyarakat, 2025)
The village of Lau Gumba faces significant ecological problems, especially related to household waste and the lack of environmental aesthetics, which require solutions that are not only technical but also based on social and religious values. Therefore, this community service adopts an ecotheological approach, which combines religious teachings with ecological awareness, through the Participatory Action Research (PAR) method. The goal of this program is to instill interfaith ecological ethics, strengthen active community participation, and redesign village environmental governance. The activities carried out include environmental care actions involving various religious groups, planting 100 trees as a form of reforestation, providing ecobins for waste management, as well as recycling waste such as used cooking oil into candles and making natural mosquito repellent sprays. The results obtained from this activity include a cleaner environment, an increase in ecological awareness of around 30%, and more harmonious interfaith social relations. These findings show that ecotheology not only serves as a strategy in sustainable environmental management, but also as an instrument for cross-faith value education. Thus, ecotheology enriches the discourse on spirituality-based environmental education, making it an effective approach in solving environmental problems while strengthening interreligious harmony.